Effect of the combined use of cryogenic + aging treatment on mechanical and damping property of Mn-Cu alloy based on response surface model - Ding, Ran; Liu, Guang-lei; Liu, Shu-cong; Ranjbar, Mostafa; Potter, Andrew; Liu, Hai-xia (Elsevier, 2025)
In this paper, the response surface method (RSM) is used to model the response surface between the target values and the cryogenic + aging treatment parameters. The effects of cryogenic + aging treatment on microstructures, mechanical, and damping properties of Mn-20Cu-5Ni-2Fe alloy are then investigated. The outcome indicates cryogenic + aging treatment can effectively enhance both mechanical and damping properties, and the optimum parameters cryogenic (-196 °C/30 h) + aging (428 °C/2 h) were obtained. The associated microstructural changes caused by the precipitated phase after the compound treatment resulted in an increase in the tensile strength from 358.3 MPa to 396.7 MPa, 38 MPa higher compared to that of the as-cast alloy. Meanwhile, it has the best damping property within a wide temperature range. At 50 °C, the internal friction value increased from 0.033 to 0.074, which was increased by 124 %. The damping strengthening mechanisms were discussed mainly from the perspective of the change in formation of {101} twins and motionable interface induced by fcc-fct transformation after the compound treatment. The obtained results provide a new reference for simultaneously improving mechanical and damping behaviors of Mn-Cu based alloys.
Keywords: 40 Engineering; 4016 Materials Engineering; 34 Chemical Sciences; 3403 Macromolecular and materials chemistry; 4018 Nanotechnology